Peran Pendidikan Agama Kristen Terhadap Pembentukan Moral Anak Sekolah Minggu - Spenerhard Makahinsade (EUANGGELION: Jurnal Teologi dan Pendidikan Kristen, 2022)
This paper is a theological analysis of the current post-modern situation and conditions showing that there has been a degradation of moral quality in the Indonesian nation, especially in hildren. Many aspects affect the symptoms of moral degradation.The role of parents in motivating Sunday School Children to Worship is not paying enough attention, marked by the lack of children attending worship/child services at the church or happy cottage. The use of less creative learning methods using only one method makes children uninteresting to hear stories and come to the children's service. Then the funding for Sunday School development did not get the attention of the church council, causing Sunday school teachers to go up and down the house to sell groceries to finance Sunday school activities.Christian religious education in moral formation essentially brings a spiritual change for the better (cognitive), which educates, teaches, and achieves a business with a future goal of noble character and fear of God. The moral formation of Sunday school children can be given formally in schools, non-formally in the church environment, namely the assembly, Sunday school teachers and informally in the family as the spearhead in the moral formation of children. These educators are required to be more creative in formulating learning patterns, methods, learning curricula and provide more funding to advance and develop Sunday school. In the application that very important role is 'exemplary' in everyday life, both the example that has been given by God Jesus as a great teacher, an example that is formally displayed by PAK; informal, and informal as well as the application of the 'dining table theory' as exemplified by the Lord Jesus. Of course, all of this cannot be separated from adjusting to the needs and growth and development of children according to conditions and characteristics in a holistic, effective and creative way.This study uses a descriptive qualitative approach, where the data obtained are in the form of an explanation of the concept or text and not numbers. The results of the study concluded that the role of Christian religious education on the moral formation of Sunday school children in the GMIM Golgotha congregation was able to develop the potential of Sunday school teachers to create the method of "Active, Creative, Effective, and Fun Learning in organizing Sunday school worship, building holistic service partnerships"